Cost effective technologies and renewable substrates for biosurfactants’ production - Banat, Ibrahim M.; Satpute, Surekha K.; Cameotra, Swaranjit S.; Patil, Rajendra; Nyayanit, Narendra V. (Frontiers in Microbiology, 2014)
Diverse types of microbial surface active amphiphilic molecules are produced by a range of microbial communities. The extraordinary properties of biosurfactant/bioemulsifier (BS/BE) as surface active products allows them to have key roles in various field of applications such as bioremediation, biodegradation, enhanced oil recovery, pharmaceutics, food processing among many others. This leads to a vast number of potential applications of these BS/BE in different industrial sectors. Despite the huge number of reports and patents describing BS and BE applications and advantages, commercialization of these compounds remain difficult, costly and to a large extent irregular. This is mainly due to the usage of chemically synthesized media for growing producing microorganism and in turn the production of preferred quality products. It is important to note that although a number of developments have taken place in the field of BS industries, large scale production remains economically challenging for many types of these products. This is mainly due to the huge monetary difference between the investment and achievable productivity from the commercial point of view. This review discusses low cost, renewable raw substrates, and fermentation technology in BS/BE production processes and their role in reducing the production cost.